Reconsideration of the scheme of the international classification of functioning, disability and health: incentives from the Netherlands for a global debate. Issue 5 (27th February 2018) - Heerkens, Yvonne F.; de Weerd, Marjolein; Huber, Machteld; de Brouwer, Carin P. M.; van der Veen, Sabina; Perenboom, Rom J. M.; van Gool, Coen H.; ten Napel, Huib; van Bon-Martens, Marja; Stallinga, Hillegonda A.; van Meeteren, Nico L. U.
Abstract: Purpose: The ICF (International Classification of Functioning, Disability and Health) framework (used worldwide to describe 'functioning' and 'disability'), including the ICF scheme (visualization of functioning as result of interaction with health condition and contextual factors), needs reconsideration. The purpose of this article is to discuss alternative ICF schemes. Method: Reconsideration of ICF via literature review and discussions with 23 Dutch ICF experts. Twenty-six experts were invited to rank the three resulting alternative schemes. Results: The literature review provided five themes: 1) societal developments; 2) health and research influences; 3) conceptualization of health; 4) models/frameworks of health and disability; and 5) ICF-criticism (e.g. position of 'health condition' at the top and role of 'contextual factors'). Experts concluded that the ICF scheme gives the impression that the medical perspective is dominant instead of the biopsychosocial perspective. Three alternative ICF schemes were ranked by 16 (62%) experts, resulting in one preferred scheme. Conclusions: There is a need for a new ICF scheme, better reflecting the ICF framework, for further (inter)national consideration. These Dutch schemes should be reviewed on a global scale, to develop a scheme that is more consistent with current and foreseen developments and changing ideas on health. Implications for Rehabilitation: We propose policy makers on community, regional and (inter)national level to consider the use of the alternative schemes of the International Classification of Functioning, Disability and Health within their plans to promote functioning and health of their citizens and researchers and teachers to incorporate the alternative schemes into their research and education to emphasize the biopsychosocial paradigm. We propose to set up an international Delphi procedure involving citizens (including patients), experts in healthcare, occupational care, research, education and policy, and planning to get consensus on an alternative scheme of the International Classification of Functioning, Disability and Health. We recommend to discuss the alternatives for the present scheme of the International Classification of Functioning, Disability and Health in the present update and revision process within the World Health Organization as a part of the discussion on the future of the International Classification of Functioning, Disability and Health framework (including ontology, title and relation with the International Classification of Diseases). We recommend to revise the definition of personal factors and to draft a list of personal factors that can be used in policy making, clinical practice, research, and education and to put effort in the revision of the present list of environmental factors to make it more useful in, e.g., occupational health care.